Deep Insight Into Long Non-coding RNA and mRNA Transcriptome Profiling in HepG2 Cells Expressing Genotype IV Swine Hepatitis E Virus ORF3 - Jiao, Hanwei; Shuai, Xuehong; Luo, Yichen; Zhou, Zhixiong; Zhao, Yu; Li, Bowen; Gu, Guojing; Li, Wenjie; Li, Mengjuan; Zeng, Hui; Guo, Xiaoyi; Xiao, Yu; et al. (Frontiers in Veterinary Science, 2021)
Swine Hepatitis E (swine HE) is a new type of zoonotic infectious disease caused by swine Hepatitis E virus (swine HEV). Open reading frame 3 (ORF3) is an important virulent protein of swine HEV but its function still is mainly unclear. In this study we generated adenoviruses ADV4-ORF3 and ADV4-NC which successfully mediated overexpression of EGFP-ORF3 and EGFP, respectively, in HepG2 cells. High throughput sequencing was used to screen for differentially expressed long noncoding RNAs (lncRNAs) and mRNAs. The cis-target genes of lncRNAs were predicted, functional enrichment (Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG)) was performed, and 12 lncRNAs with statistically significant different expression (p value ≤ 0.05 and q value ≤ 1) were selected for further quantitative real-time reverse transcription (qRT-PCR) validation. In HepG2 cells, we identified 62 significantly differential expression genes (DEGs) (6,564 transcripts), and 319 lncRNAs (124 known lncRNAs and 195 novel lncRNAs) that were affected by ORF3, which were involved in systemic lupus erythematosus, staphylococcus aureus infection, signaling pathways regulating pluripotency of stem cells, the PPAR signaling pathway, and platinum drug resistance pathways. Cis-target gene prediction identified 45 lncRNAs corresponding to candidate mRNAs, among which 8 were validated by qRT-PCR: LINC02476 (two transcripts), RAP2C-AS1, AC016526, AL139099, and ZNF337-AS1 (3 transcripts). Our results revealed the lncRNA profile in host cells affected by ORF3, swine HEV-ORF3 might affect the pentose and glucuronate interconversions and mediate the formation of obstructive jaundice by influencing the bile secretion, which will help to determine the function of ORF3, and the infection mechanism and treatment of swine HE.